Navigating water crisis, cholera, and refugee context: Lessons from Nakivale refugee settlement, Isingiro District, Uganda. - Freda Loy Aceng; Bonny Kintu; James Habumugisha; Stephen Kayanja; Flavia Wanyoto; Moureen Asiimire; Emmanuel Maurice Ochien; Bernard Amaga; Sam Kwesiga; Sylivia Kemigisha; Stella Maris Lunkuse; Barbara Namara; et al. (PLOS Global Public Health)
Inadequate safe water supply and cholera outbreaks are significant contributors to ill health in displaced populations, exacerbating the vulnerability of refugees fleeing conflicts. In November 2021, the Nakivale Refugee Settlement faced a cholera outbreak and water scarcity, putting displaced persons at risk of ill health. This study aimed to investigate the lessons learned from this incident and identify pathways to prevent future outbreaks, ultimately safeguarding the lives and well-being of vulnerable populations. A descriptive cross-sectional study analysed epidemiological data from the Uganda Ministry of Health, investigating the cholera outbreak among refugees in Nakivale Refugee Settlement, Isingiro district, from November 3rd to December 2nd, 2021. The outbreak affected 173 refugees, primarily in Nyarugugu B and C villages, with consumption of contaminated lake water identified as the likely cause. Inadequate access to clean water and sanitation facilities exacerbated the outbreak, which disproportionately affected individuals aged 10-19 years (30.1%) and females (65%). Promotion of safe water, sanitation, and oral cholera vaccination campaigns effectively controlled the outbreak. This study highlights the critical importance of providing refugees with access to safe water and sanitation infrastructure to prevent cholera outbreaks. Timely implementation of oral cholera vaccination campaigns and enhanced water management systems are crucial to preventing future outbreaks in refugee settlements.